Kenyan English domains of use, forms, and users' attitudes - Michieka, Martha; Mecha, Evans Gesura (Lexington Books, 2021)
"This volume treats the sociolinguistic reality of Kenyan English. The contributors give the readers a rare glance into various contexts of English language use, such as school classrooms, radio stations, an urban pulpit, and a multilingual family setting"--